Capital Account Policies in Chile Macro-financial considerations along the path to liberalization - Carriere-Swallow, Yan (IMF Working Papers; Working Paper, 2013)
This paper recounts Chile's experience with capital account policies since the 1990s. We present how two external shocks were confronted under very different macroeconomic and capital account frameworks. We show that during the 1997-98 Asian-LTCM-Russia crisis, a closed capital account and relatively rigid exchange rate severely constrained the monetary policy response to the shock, aggravating the fall in domestic demand. During the 2008-09 crisis, a full-fledged inflation targeting framework allowed the authorities to implement a significant countercyclical response. We argue that domestic stability considerations lay behind the policy regime switch toward capital account liberalization from 1999 onwards.